A preliminary study to develop an intervention to facilitate communication between couples in advanced cancer. Issue 5 (October 2015) - Mowll, Jane; Lobb, Elizabeth A.; Lane, Lisbeth; Lacey, Judith; Chochinov, Harvey M.; Kelly, Brian; Agar, Meera; Links, Matthew; Kearsley, John H.
Abstract: Objective: Psychosocial interventions directed to couples where one has advanced cancer can reduce distress, enhance communication, and provide an opportunity for relational growth. The present study aimed to develop an intervention to facilitate communication about living with advanced cancer using the Patient Dignity Inventory (PDI) as the focus of a clinical interview with couples toward the end of life. Method: Couples were recruited from oncology and palliative care services at a Sydney hospital. After the PDI was developed and manualized as an intervention for couples, the PDI–Couple Interview (PDI–CI) was delivered by a clinical psychologist and comprised the following: (1) the patient completed the PDI; (2) the patient's identified partner completed the PDI about how they thought the patient was feeling; and (3) the clinician reviewed the results with the couple, summarizing areas of concurrence and discordance and facilitating discussion. Results: Some 34 couples were referred, of which 12 consented, 9 of whom completed the clinical interview. Reported benefits included enabling couples to express their concerns together, identifying differences in understanding, and giving "permission to speak" with each other. The focus of the interview around the PDI provided a structure that was particularly acceptable for men. Most couples confirmed that they were "on the same page, " and where differences were identified, it provided a forum for discussion and a mutual understanding of the challenges in managing advanced cancer within a supportive context. Significance of Results: Participant couples' experiences of the PDI–CI provide valuable insight into the benefits of this intervention. This preliminary study indicates that the intervention is a relatively simple means of enhancing closer communication and connection between couples where one has advanced cancer and may be an important adjunct in helping prepare couples for the challenges inherent toward the end of life. Further investigation of feasibility with a larger sample is recommended.